Analysis of conditions and prerequisites organization of independent work of future teacher-engineers in the process of learning pedagogical disciplines (Pedagogy of Higher and Secondary Education, 2013)
Finohyeyeva T. E. Analysis of conditions and prerequisites organization of independent work of future teacher-engineers in the process of learning pedagogical disciplines.On the basis of studies of modern pedagogical works carried out to analyze the conditions and prerequisites for the effective organization of independent work of future teacher-engineers in the process of learning pedagogical disciplines. The author offers his own vision of the pedagogical problem-specific training in engineering-pedagogical higher education.
Keywords: engineering and teacher education; self study; teacher-engineer; an organization of independent work; teaching discipline